Therapeutic targeting of tumor suppressor genes. Issue 9 (29th December 2014) - Morris, Luc G. T.; Chan, Timothy A.
Abstract : Carcinogenesis is a multistep process attributable to both gain‐of‐function mutations in oncogenes and loss‐of‐function mutations in tumor suppressor genes. Currently, most molecular targeted therapies are inhibitors of oncogenes, because inactivated tumor suppressor genes have proven harder to "drug." Nevertheless, in cancers, tumor suppressor genes undergo alteration more frequently than do oncogenes. In recent years, several promising strategies directed at tumor suppressor genes, or the pathways controlled by these genes, have emerged. Here, we describe advances in a number of different methodologies aimed at therapeutically targeting tumors driven by inactivated tumor suppressor genes. Cancer 2015;121:1357–1368. © 2014 American Cancer Society . Abstract : In recent years, several promising strategies directed at tumor suppressor genes, or the pathways controlled by these genes, have emerged. Here, we describe advances in a number of different methodologies aimed at therapeutically targeting tumors driven by inactivated tumor suppressor genes.